OPTIMIZING THE DIET FOR PAITIENTS WITH DIGESTIVE SYSTEM GATROINTESTINAL TRACT DISORDERS IN HOT CLIMATE CONDITIONS - Baxtiyor Xolnazarovich Shoymardanov; Guli Islamovna ShayKhova (Innovate Conferences, 2025)
Against the backdrop of global climate warming.